2005
DOI: 10.1161/01.hyp.0000164572.92049.29
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Inhibitors Attenuate Angiotensin II–Induced Oxidative Stress, Hypertension, and Cardiac Hypertrophy in Rats

Abstract: Abstract-Angiotensin II is an important oxidative stress mediator. Our previous studies have indicated that the potent antioxidative properties of acetylsalicylic acid play an important role in its cardiovascular protective effects. There are some ongoing controversies concerning the use of selective cyclooxygenase-2 inhibitors in cardiovascular disease. The aim of this study was to determine whether the cyclooxygenase-2 selective inhibitors rofecoxib and nimesulide possess antioxidative and cardiovascular pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 31 publications
3
49
0
2
Order By: Relevance
“…A previous report showed that COX2 plays a significant role in AngIIinduced NADPH oxidase-derived O2-production (Wu et al 2005). Rofecoxib (Selective COX2 inhibitors) blocked superoxide formation and reduced cardiac hypertrophy, which provided antioxidative properties during enhanced AngII activity (Wu et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that COX2 plays a significant role in AngIIinduced NADPH oxidase-derived O2-production (Wu et al 2005). Rofecoxib (Selective COX2 inhibitors) blocked superoxide formation and reduced cardiac hypertrophy, which provided antioxidative properties during enhanced AngII activity (Wu et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a high prevalence of diseases, such as hypertension, diabetes, atherosclerosis, osteoarthritis and cancer, in elderly patients promotes an increased use of NSAIDs [14] . Reports on the effect of NSAIDs on the cardiovascular system are controversial [15][16][17][18] . NSAIDs cause increased blood pressure by blocking the synthesis of prostaglandins that regulate vascular tone and sodium excretion [19,20] .…”
Section: Introductionmentioning
confidence: 99%
“…Desta forma, a via cicloxigenase-2 parece também participar do estresse oxidativo e dos efeitos deletérios ao sistema cardiovascular (Wu et al, 2005).…”
Section: Ações E Interações Da Ang II No Sistema Cardiovascularunclassified
“…Observações oriundas, principalmente, de modelos experimentais, têm estimulado pesquisas visando o potencial terapêutico dos anti-oxidantes, como o ácido caféico, antiiflamatórios e mais enfaticamente os medicamentos anti -TNF-α (Li et al, 2000;Li et al, 2005;Wu et al, 2005).…”
Section: Ações E Interações Da Ang II No Sistema Cardiovascularunclassified